AlGaN/AlN heterostructures: an emerging platform for integrated photonics - Sinan Gündoğdu; Sofia Pazzagli; Tommaso Pregnolato; Tim Kolbe; Sylvia Hagedorn; Markus Weyers; Tim Schröder (npj Nanophotonics)
Abstract We introduce a novel material for integrated photonics and investigate aluminum gallium nitride (AlGaN) on aluminum nitride (AlN) templates as a platform for developing reconfigurable and on-chip nonlinear optical devices. AlGaN combines compatibility with standard photonic fabrication technologies and high electro-optic modulation capabilities with low loss over a broad spectral range, from UVC to long-wave infrared, making it a viable material for complex photonic applications. In this work, we design and grow AlGaN/AlN heterostructures and integrate several photonic components. In particular, we fabricate edge couplers, low-loss waveguides, directional couplers, and tunable high-quality factor ring resonators. These devices will enable nonlinear light-matter interaction and quantum functionality. The comprehensive platform we present in this work paves the way for photon-pair generation applications, on-chip quantum frequency conversion, and fast electro-optic modulation for switching and routing classical and quantum light fields.